DETERMINATION OF RADIONUCLIDES IN SOME SELECTED DUMPSITES WITHIN KANO METROPOLIS, KANO STATE NIGERIA - Muhammad, Aminu Shuaibu; Nura, Abdulkadir Muhammad; Muhammad, Sunusi Dayyab (FUDMA JOURNAL OF SCIENCES, 2025)
This research investigated the emission of radiation from refuse dumpsites in some selected areas in Kano metropolis. The readings were taken using Geiger Muller tube detector at gonad level (about 1 meter above the ground level) and at an interval of 5m away from point of reference up to 20m in five sampling locations; coded as RD1, RD2, RD3, RD4 and RD5 respectively while the natural radioactivity concentrations were determined using a gamma ray spectrometer with two calibration point sources, Cs-137 and Co-60. The results indicated that the ranges of activity concentrations of 40K, 226Ra and 232Th in the samples were 304.66 – 460.96 BqKg-1, 18.57 – 32.72 BqKg-1 and 12.22 – 53.63BqKg-1 respectively. The highest activity concentration of 226Ra, 232Th and 40K were found to be 32.72±3.12 Bqkg-1, 53.63±3.49 Bqkg-1 and 460.96±7.78 Bqkg-1 respectively which obtained from RD2 and RD4 locations. However, the highest magnitude of Radium Equivalent Dose (Req.) of 137.60 Bqkg-1 at RD2 was found to be below the permissible limit of 370 BqKg-1 as recommended by UNSCEAR, (2000). Moreover, the highest average value of the background radiation detected at RD1 and RD3 was 0.414mSv/year which is below the ICRP (2006) bench mark of 3.0mSv/year. Therefore, the radionuclide activity concentration and the average exposure rate may not be hazardous. These results will help the health and environmental agencies in developing waste management systems.